PERBEDAAN PENGETAHUAN DAN SIKAP PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) ANTARA SANTRI PUTRA DAN SANTRI PUTRI - Zulfa Husni Khumayra; Madya Sulisno (Jurnal Keperawatan Diponegoro, 2012)
Boarding School  can also be a threat of disease transmission if not properly managed due to the easy transmission caused by  the density and the environment are inadequate, so inculcate “Perilaku Hidup Bersih dan Sehat (PHBS)” is an absolute requirement  to do because Boarding  school’s students are a risk group of being diseases contracted. Knowledge and  attitudes have a significant influence on the success of a groundbreaking program because of poor knowledge can  be obstructed and  bring on failure to “Perilaku Hidup Bersih dan Sehat (PHBS)”. In fact,knowledge is not always can change into the attitudes and attitudes is not always can change into action. A gender can distinguish the behavior and characteristic as a result of behavior.The purpose of the study to know the difference “Perilaku Hidup Bersih dan Sehat (PHBS)”between students girls and boys.Results showed that there was no significant difference PHBS knowledge between students boys and girls of students with p = 0.267 (p ≥ 0.05), there are significant differences between students attitudes PHBS boys and girls with p-value = 0.021 (p ≤ 0.05). Knowledge and attitudes regarding “Perilaku Hidup Bersih dan Sehat (PHBS) at enaought categories so can do health education about PHBS.